Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø§Ù„Ù…Ø¯ Ø§Ù„Ù…Ø¹Ø±ÙÙŠ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ ÙˆØ§Ù„ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© - As-Tsistry, Shaleh (Jurnal Pendidikan Islam, 2016)
This study stems from the assumption that Arabic is the source of Islamic culture. the Relationship between them is so close and indeed they are inseparable. Arabic serves as a vessel of Islam and it goes without saying that it is used to deliver Qur'an. In addition it is used by the prophet for communication. The purpose of this study is to determine the extent of the relationship between Arabic and Islamic thought particularly Islamic educatio. This study applied library research by examining the discourse and literature related to the research problem put forward. The results of this study reinforce the influence of Arabic on the development of Islamic education particularly its influence in studying and exploring the Islamic sciences. The Â establishment of various Islamic educational institutions as a place to learn Arabic , Islamic thought and other Islamic sciences supports the result of this study. Â